Rare Skin Fistulas Relating to Ascending Colonic Carcinoma: An Unusual Mode of Revelation. (March 2018) - Zhou, Hanlei; Shao, Huawei; Ho, Jon Kee; Wang, Xingang; Han, Chunmao; Chen, Guoxian
Chronic or nonhealing wounds is a complex disease influenced by a multitude of factors, such as infection, ischemia, malnutrition, and diabetes and infrequently relates to retroperitoneal carcinoma. We present a case of an adenocarcinoma of ascending colon in a 68-year-old male who had lumbago and waist fistulas with retroperitoneal abscesses preceding other signs or symptoms of colonic malignancy. Supplemental information regarding the diagnosis and treatment of nonhealing wounds and colon carcinoma has also been included in the report. Adenocarcinoma of ascending colon is rarely associated with nonhealing wounds; nevertheless, it should be considered in cases with long-term healing complications. Precise diagnostic deliberation is crucial in the management and treatment of all chronic and long-term nonhealing lesions, and appropriately performed biopsies are essential to determine whether malignancy is the primary cause.